(untitled) (Research, Society and Development, 2025)
The study aimed to analyze the epidemiological profile of pertussis cases in Brazil in 2024 and the incidence rate, proposing more effective prevention and control strategies. This was a cross-sectional, descriptive epidemiological study using secondary databases. Public data provided by the Department of Information Technology of the Unified Health System (DATASUS) and the Notifiable Diseases Information System (SINAN) were used. Analysis of these data revealed that Brazil recorded 6,939 pertussis cases in 2024, of which over 90% were cured. The number of cases grew steadily throughout the year, peaking at 1,544 (22.1%) in October. The highest incidence of the disease was observed in females aged 10 to 14. The state of Paraná accounted for the majority of cases, and most confirmations were made through laboratory criteria. This analysis showed that, compared to previous years, pertussis showed changes in age and regional profiles, but maintained its seasonality. Therefore, public health strategies should focus on implementing booster vaccination campaigns targeting the most vulnerable populations.